ChemInform Abstract: CoxCu1‐xCr2S4 Nanocrystals: Synthesis, Magnetism, and Band Structure Calculations. Issue 2 (14th January 2014) - Ramasamy, Karthik; Sims, Hunter; Gupta, Ram K.; Kumar, Dhananjay; Butler, William H.; Gupta, Arunava
Abstract Nanocrystals of CoxCu1‐xCr2S4 are prepared over the entire composition range by reaction of appropriate amounts of CuCl2, CoCl2, and CrCl3 in the presence of octadecylamine (360 °C, N2 atmosphere) followed by injection of 1‐dodecanethiol and further heating for 1 h.